The Impact of the Iraqi-Turkish Relationship on their hydro political relations after 2003 - Dr. Luay Ali AlDalooi (Tikrit Journal For Political Science, 2022)
This paper analyses the water relations between Iraq and Turkey by applying the Framework of Hydro-hegemony, which reveals that their comprehensive bilateral political relations shape their hydropolitical ties to a great extent. After World War I, Turkey approached Iraq to ally against the rise of Soviet power and cooperated in the water field to sign the 1946 agreement. When the Justice and Development Party came to power, particularly after the American invasion, Turkey employed soft diplomacy. In its foreign policy towards Iraq, Turkey employed a blend of soft power and material power, mainly military might. Thus, this was reflected in their water relations. Furthermore, Turkey used water as a strategic tool for dealing with Iraq. It neither negated water cooperation with Iraq nor elevated this cooperation to an institutional formula embodied in an explicit agreement.